For questions 14-15, find the simplified form of each expression.

(3/2b^4)^3

(3/5y^4)^-2

5 answers

Reiny, Steve!! I need help!
(3/2b^4)^3
= (27/8)b^12

(3/5y^4)^-2
= 1/(3/5y^4)^2
= 1/( (9/25)y^8
= 25/(9y^8)
or
(25/9)y^-8
Can you help me with some graph ones?
[ ( 3 / 2 ) b ^ 4 ] ^ 3 =

[ ( 3 ^ 3 ) / ( 2 ^ 3 ) ] * ( b ^ 4 ) ^ 3 =

( 27 / 8 ) * b ^ ( 4 * 3 ) =

( 27 / 8 ) * b ^ 12 =

27 b ^ 12 / 8

( 3 / 5 y ^ 4 )^ ( - 2 ) =

[ ( 3 ^ ( - 2 ) ] / [ ( 5 ^ ( - 2 ) ] * [ y ^ 4 ^ ( - 2 ) ] =

( 1 / 3 ^ 2 ) / ( 1 / 5 ^ 2 ) * y ^ [ 4 * ( - 2 ) ] =

( 1 / 9 ) / ( 1 / 25 ) * ( y ^ - 8 ) =

[ ( 1 * 25 ) / ( 1 * 9 ) ] * 1 / y ^ 8 =

( 25 / 9 ) * 1 / y ^ 8 =

25 / 9 y ^ 8
Fractions

1-(2/3+1/5)=